主体身份及关联关系识别方法、装置、设备和介质 (2024)
本发明公开了一种主体身份及关联关系识别方法，该方法包括：获取主体要素信息并输入主体身份识别引擎，通过主体身份识别引擎内载的标准数据库的数据库信息进行匹配。通过主体身份识别引擎将匹配的数据库信息对主体要素信息进行更新，得到精确识别的主体身份。通过股权穿透算法计算主体身份的外部关联关系，将所有外部关联关系与主体身份进行关联，得到目标关联群组。获取与主体身份及外部关联关系关联的内部关联存储信息，根据内部关联存储信息筛选出内部关联部门，将内部关联部门与目标关联群组关联，得到目标关联网络。本发明可帮助金融机构提前捕捉风险，确保投资安全。此外，还提出了主体身份及关联关系识别装置、设备和介质。 The invention discloses a main body identity and association relationship identification method, which comprises the following steps: acquiring main body element information, inputting the main body element information into a main body identity identification engine, and matching the main body element information through database information of a standard database loaded in the main body identityidentification engine; and updating the main body element information by using the matched database information through a main body identity recognition engine to obtain a precisely recognized main body identity; and calculating external association relationships of the subject identity through a stock right penetration algorithm